PERBANDINGAN NILAI BUDAYA KARYAWAN HOTEL DI SEMINYAK DAN UBUD - Made Arya Astina; Anak Agung Gede Wijaya (Jurnal Ilmiah Hospitality Management, 2019)
The research on this tourism human resource is titled Comparison of Employee Culture value hotels in Seminyak and Ubud. This research is a quantitative study conducted in two tourist destinations in Bali namely Seminyak and Ubud area. Data collection techniques are carried out by distribution of polls, and literature studies. The research period will be held in August 2019 – October 2019. As for the research subject specified is a number of each of the 60 employees of the hotel in both areas. Seminyak and Ubud area were chosen as the location of the research with several considerations: 1) Seminyak and Ubud are the main tourist destinations in Bali, 2) The growth of the number of hotels in both regions is equally fast, 3) the culture owned by hotel employees In Seminyak and Ubud need to be analyzed for product development (service). The theory used in the study was the cultural value theory of Hofstede. Angket (questionnaire) used to refer to VSM (Value Survey Mudule) developed by Hofstede. Since the province of Bali relies on the tourism sector for its region's major income, the research is important because human resources are an important component of the service. This research resulted in several findings on the similarities and differences in the value of hotel employees ' culture in Seminyak and Ubud areas.